The Oxford handbook of Spanish politics - Muro, Diego 1975-; Lago, Ignacio (Oxford handbooks online, 2020)
'The Oxford Handbook of Spanish Politics' provides a comprehensive and comparative overview of the Spanish political system through the lens of political science. This handbook examines Spanish politics and government since the transition to democracy. The volume studies the political history, institutional changes, bureaucratic decision-making, political behaviour, and foreign affairs of Spain. The introductory chapter provides an overview of the main themes of democratic Spain and discusses the end of Spanish exceptionalism. It also introduces Spanish politics to an international audience of scholars and practitioners to be considered either in its own right or as a case among others in a comparative perspective